Computer simulation of MC-SNICS for performance improvements - Han, B. X.; Southon, J. R.; Roberts, M. L.; von Reden, K. F. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2007)
Increasing ion source current output while keeping the beam emittance small is a key for improving measurement throughput and quality of an accelerator mass spectrometry (AMS) system. The NEC MC-SNICS ion sources have widely been used for AMS around the world. In this work, a computer simulation study on MC-SNICS ion source was carried out using the code PBGUNS. The primary Cs+ beam is simulated as space-charge limited emission from the ionizer surface. The secondary negative ion beam is simulated in the presence of the space-charge induced by both the primary and the secondary beam. Two different configurations of the MC-SNICS have been studied: the original factory version and the UC Irvine modified version. The latter has a 0.668 in. radius spherical ionizer and an immersion lens at cathode potential with the original Cs focus lens removed. Simulation showed that the modified version provides more intense and better focused Cs+ beam at the cathode target, hence higher negative ion production from the sample by sputtering. The new arrangement of Einzel-preacceleration section of the MC-SNICS at UC Irvine was also simulated and discussed. Simulation results are in good agreement with the experimental observations made at UC Irvine. Hints for selection of an immersion lens geometry have been obtained. (c) 2007 Elsevier B.V. All rights reserved.
200swTimes Cited:8Cited References Count:8